REACTION BETWEEN ULTRAMAFIC ROCK AND FRACTIONATING BASALTIC MAGMA I. PHASE RELATIONS, THE ORIGIN OF CALC-ALKALINE MAGMA SERIES, AND THE FORMATION OF DISCORDANT DUNITE - Kelemen P.B. (My University, 1990)
This paper presents results of modelling reaction between peridotite and fractionating tholeiitic basalt in simple and complex silicate systems. Reactions are outlined in appropriate binary and ternary silicate systems. In these simple systems, the result of reactions between ‘basalt’ and ‘peridotite’ may be treated as a combination of Fe-Mg exchange and mass transfer reactions at constant Fe/Mg. Fe-Mg exchange in ternary and higher-order systems is nearly isenthalpic, and involves a slight decrease in magma mass at constant temperature. Mass transfer reactions, typically involving dissolution of orthopyroxene and consequent crystallization of olivine, are also nearly isenthalpic in ternary and higher-order silicate systems, and produce a slight increase in the magma mass at constant temperature. The combined reactions are essentially isenthalpic and produce a slight increase in magma mass under conditions of constant temperature or constant enthalpy. Initial liquids saturated in plagioclase+olivine will become saturated only in olivine as a result of near-constant-temperature reaction with peridotite, and crystal products of such reactions will be dunite. Liquids saturated in clinopyroxene+olivine will remain on the cpx-ol cotectic during reaction with peridotite, but will crystallize much more olivine than clinopyroxene as a result of reaction, i.e., crystal products will be clinopyroxene-bearing dunite and wehrlite rather than olivine clinopyroxenite, which would be produced by cotectic crystallization. The Mg/Fe ratio of crystal products is ‘buffered’ by reaction with magnesian peridotite, and dunites so produced will have high, nearly constant Mg/Fe. Production of voluminous magnesian dunite in this manner does not require crystal fractionation of a highly magnesian olivine tholeiite or picrite liquid. Combined reaction with ultramafic wall rock and crystal fractionation due to falling temperature produces a calc-alkaline liquid line of descent from tholeiitic parental liquids under conditions of temperature, pressure, and initial liquid composition which would produce tholeiitic derivative liquids in a closed system. Specifically, closed-system differentiates show iron enrichment at near-constant silica concentration with decreasing temperature, whereas the same initial liquid reacting with peridotite produces silica-enriched derivatives at virtually constant Mg/Fe. Reaction between fractionating basalt and mafic to ultramafic rock is likely to be important in subduction-related magmatic arcs, where tholeiitic primary liquids pass slowly upward through high-temperature wall rock in the lower crust and upper mantle. Although other explanations can account for chemical variation in individual calc-alkaline series, none can account as well for the characteristics shared by all calc-alkaline series. This process, if it is volumetrically important on Earth, has important implications for (Phanerozoic) crustal evolution: sub-arc mantle should be enriched in iron, and depleted in silica and alumina, relative to sub-oceanic mantle, acting as a source for sialic crust It is probable that inter-occanic magmatic arcs have basement similar to alpine peridotite, in which sub-oceanic mantle has been modified by interaction with slowly ascending basaltic liquids at nearly constant temperature. Discordant dunite bodies in alpine pendotite may record extraction of sialic crust from the Earths upper mantle.